Enhancing English Proficiency And Academic Performance Through Collaborative Language Learning In Grade 12 - Naheed Haq , Dr. Uranus Saadat (Migration Letters, 2024)
As education has the primary duty of providing students with the information and abilities necessary to prosper in this rapidly changing environment, educational patterns as well as objectives must keep pace with cultural as well as technological change. This study looks into how collaborative language learning affects students’ academic performance and English competence in Grade 12 in Khyber Pakhtunkhwa (KPK), Pakistan. The study sampled 300 students using a quasi-experimental design using a quantitative research approach. The academics were split into major two groups: the one was experimental group (collaborative learning) as well as the second group was the control group (conventional learning). Important results show that studying a language collaboratively improves scholastic performance and English proficiency. However, there was n[1]o significant gender difference in pedagogical performance, female students scored higher on the English proficiency test than their male counterparts. There are significant relationships between academic achievement, student involvement, and English competence, as demonstrated by statistical analyses using t-tests, ANOVA, and regression. The study promotes gender-specific educational interventions by highlighting the value of collaborative learning in language skill development and academic performance. To improve language competence and academic accomplishment, recommendations place a strong emphasis on the necessity of teacher training, customized instruction, and creating collaborative learning environments. The cross-sectional design and small sample size of the study are limitations that point to the need for larger, longer investigations to demonstrate causation and generalize the results. The results provide insightful information that policymakers and educators may use to improve English language instruction in a variety of cultural and educational contexts.